Выражение: (a-1/a+1-a/a-1)*a+1/1-3a /-деление *-умножение

oriano oriano    3   26.07.2019 02:10    0

Ответы
dimazhulin1609 dimazhulin1609  03.10.2020 13:08
(a-1/a+1-a/a-1)*a+1/1-3a
(a-1/a-1)a-3a+1
a(a-4)
ПОКАЗАТЬ ОТВЕТЫ
Явсёзнаю0 Явсёзнаю0  03.10.2020 13:08
 (a-1)(a-1)/a  +a(1-a)/( a-1)  * (a+1)/(1-3a)=(a-1)^+a(1-a)/a(a-1) *(a+1)/1-3a=   a^-2a+1+a-a^ /a(a-1) *(a+1)/1-3a = -(a-1)/a(a-1) * (a+1)/1-3a=-1/a * (a+1)/1-3a=-1(1-3a) * a(a+1) /a(1-3a)=-(a+1)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра